PENGARUH BERBAGAI INTENSITAS CAHAYA TERHADAP PERUBAHAN STRUKTUR ANATOMI DAUN TANAMAN GAHARU (Gyrinops versteegii (Gilg.) Domke) - Taufik Samsuri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
Indonesia's forests are tropical forests rich in yields that have a high economic value to reach the third rank of the world. One of the non-timber forest products is Gaharu (Gyrinops versteegii). Agarwood has many benefits as a producer of perfumes, incense for prayer and some other goods that have a high economic value. The aim of this research is to know the difference of anatomical structure of eagle leaf which is treated in various intensity of light. This research was conducted at Evaluation-Collection Garden of Plant Breeding, Faculty of Agriculture, University of Mataram from August 21, 2007 until September 25, 2008. The research was designed using RAK (Group Random Design) consisting of 3 blocks, each block was 5 light intensity treatment 20% ; 40%; 60%; 80% and 100% of each treatment there are 3 replications, so that obtained 3 x 5 x 3 = 45 sample units. Data obtained from the study were analyzed using Analisys of variance (ANOVA) and tested further with BNT at 5% significant level. The parameters observed included stoma density, trichome density, stoma type, pile cell height, thick epidermal upper and lower epidermal thickness, the results of the analysis showed that each treatment given to gaharu plants showed a significant difference in the anatomical structure of the leaves. The conclusion of the research result is the intensity of light effect on the changes on the anatomical structure of gaharu leaf, especially on the parameters.